2007
DOI: 10.2332/allergolint.o-06-431
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Bronchodilator Responsiveness and Quality of Life in Chronic Obstructive Pulmonary Disease

Abstract: Those who have FVC that respond to bronchodilator at rest might result in an improvement of HRQoL after treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 39 publications
1
7
1
Order By: Relevance
“…Although these observations have to be verified in a wider range of COPD patients, including women, we believe that this parameter is important and should be included in the daily practice of pulmonary medicine and promoted by GOLD. 11 hand, in stable COPD patients, Omata et al [37] showed a cross-sectional relationship between BD reversibility and the respective items of health-related quality of life (HRQoL) and activities of daily living. Interestingly, the acute FVC response to BD was significantly correlated with numerous HRQoL items, which was not the case for the FEV 1 response.…”
Section: Discussionmentioning
confidence: 99%
“…Although these observations have to be verified in a wider range of COPD patients, including women, we believe that this parameter is important and should be included in the daily practice of pulmonary medicine and promoted by GOLD. 11 hand, in stable COPD patients, Omata et al [37] showed a cross-sectional relationship between BD reversibility and the respective items of health-related quality of life (HRQoL) and activities of daily living. Interestingly, the acute FVC response to BD was significantly correlated with numerous HRQoL items, which was not the case for the FEV 1 response.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated a significant relationship between poor lung function and worsened health and economic outcomes in patients with COPD [2-13], but few have investigated whether changes in lung function associated with an intervention are correlated with changes in such endpoints [12-15]. There is good evidence that declining lung function leads to worsened patient outcomes, but a surprising lack of evidence that improvements in lung function are correlated with improvements in symptomatic outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The role of lung function, and of volume and flow reversibility in predicting disease progression of COPD (e.g. rate of lung function; health status decline, and rate of exacerbations) has been already clarified [Serviddio et al 2006;Calverley et al 2003]: obviously, an improved response to bronchodilators is presumed to impact positively in COPD patients in terms of daily symptoms and quality of life [Omata et al 2007]. …”
Section: Original Researchmentioning
confidence: 99%